GENERASI Z DAN PEMELIHARAAN RELASI ANTAR GENERASI DALAM PERSPEKTIF BUDAYA JAWA - Lintang Citra Christiani; Prinisia Nurul Ikasari (Universitas Tidar, 2020)
So far, generation Z stick to the stereotypes of antisocials, instant, lazy, and difficult to communicate with older generation. Generational differences often cause problems because each generation is attached to certain ideal values that are very likely to be different from one another. This study aims to understand the communication style of generation Z in Magelang City and the maintenance of relationships with previous generations (baby boomers, X, and Y generations). The theory of generation development, the concept of communication style, and relationship maintenance theory are used as analysis tools. This study uses a qualitative descriptive research type with a phenomenological approach to explain the social phenomena. The results show that Generation Z avoids the dominant style of communication. “Ngemong” then becomes the key as well as the middle way for the older generation to maintain a harmonious relationship with generation Z. Generation Y can act as an intermediary for both generation X and baby boomers towards the minding process in maintaining relations between generations.